Pemanfaatan Media Sisa Tanaman Padi Gogo Periode Pertama Sebagai Media Tanam Periode Kedua (Oryza Sativa L) - Fu'ad Maulidin; Anis Sholihah; Agus Sugianto (AGRONISMA, 2019)
This study aims to determine the effect of water cabbag(Pistia stratiotes) and straw mixture compost with various compositions of the first period of compost residue on the growth and yield of upland rice in the second period. added control and NPK fertilizer, with the following treatment: control = Without compost and NPK, R1-= 100% water cabbag(Pistia stratiotes), R2- = 75% water cabbag(Pistia stratiotes) + 25% straw, R3- = 50% water cabbag(Pistia stratiotes) + 50% straw, R4- = 25% water cabbag(Pistia stratiotes) + 75% straw, R5- = 100% straw, and R6 = NPK. The results showed that 100% of the compost residual straw on the first planting period had a different effect on the growth and yield of rice plants, where the mixture of organic matter with a composition of 100% straw was first planted with upland rice 5,84 grain weight per ha -1) significantly different from fertilizer NPK 5.04 Grain weight per ha (ton.ha-1)